Does household food insecurity influence nutritional practice of children age 6 to 23 months in Bangladesh? - Chowdhury, Mohammad Rocky Khan; Kabir, Russell; Papadopoulas, Konstantinos; Arafat, SM Yasir; Kader, Manzur; Alam, Mohbub; Mondal, Md Nazrul Islam (South East Asia Journal of Public Health, 2017)
To examine the prevalence of household food insecurity (HHFI) among children aged between 6-23 months in Bangladesh. This paper also aims to identify the individual, household and community levels determinants of HHFI and the association between nutritional behavior and HHFI. Bangladesh Demographic Health Survey (BDHS), 2011 was used for this research. A total of 2,344 children were selected for analysis. Statistical analysis and tests were guided by the nature of the variables. Finally, logistic regression analysis was used to find out the association between independent variables and outcome. The overall prevalence of HHFI was 36.3% (95% CI: 33.6-39.0) among the participants (children). The prevalence of HHFI was significantly higher among children who did not receive nutritional items. In contrast, HHFI was more prevalent among children who were breastfed (37.0%) as compared to non-breastfed. Binary logistic regression analysis showed that children of illiterate mothers (adjusted OR: 2.20, 95% CI: 1.17-4.10), illiterate fathers (adjusted OR: 2.27, 95% CI: 1.41-3.66) and socio-economically poor families (adjusted OR: 11.35, 95% CI: 7.20-17.91) were more at risk of experiencing HHFI, whereas, rural children (adjusted OR: 0.72, 95% CI: 0.57-0.93) were more protective. In the adjusted logistic regression model, children who did not receive juice (adjusted OR: 1.54, 95% CI: 1.09-2.16) had experienced HHFI. The prevalence of HHFI among children is still high in Bangladesh. Therefore, to achieve the Millennium Development Goals, the Government of Bangladesh should priorities HHFI as a major public health issue. Strong collaborations among various stakeholders are also crucial to improve the situation. South East Asia Journal of Public Health Vol.6(2) 2016: 53-60